2022
DOI: 10.2142/biophysico.bppb-v19.0014
|View full text |Cite
|
Sign up to set email alerts
|

Dorsolateral prefrontal cortex sensing analgesia

Abstract: Chronic pain often has an unknown cause, and many patients with chronic pain learn to accept that their pain is incurable and pharmacologic treatments are only temporarily effective. Complementary and integrative health approaches for pain are thus in high demand. One such approach is soft touch, e.g., adhesion of pyramidal thorn patches in a pain region. The effects of patch adhesion on pain relief have been confirmed in patients with various types of pain. A recent study using near-infrared spectroscopy reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…Previous studies have suggested that humans and other mammals feel comfort (i.e., pleasure) when the perception of mild skin stimulation is sent to the brain via C fibers [ 30 , 31 ]. It is possible that, in such a situation, OXT is released not only from the hypothalamus but also in the DRG.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that humans and other mammals feel comfort (i.e., pleasure) when the perception of mild skin stimulation is sent to the brain via C fibers [ 30 , 31 ]. It is possible that, in such a situation, OXT is released not only from the hypothalamus but also in the DRG.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed that DRG neurons contain oxytocin and its related receptors including TRP channels. Oxytocin has been reported to play some roles in the DRGs [ 28 – 32 ], because oxytocin acts on DRG neurons and suppresses the firing of action potentials [ 33 , 34 ]. The expression of oxytocin was also confirmed in DRG neurons [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the first publication of “Cancer pain relief”, it has become quite evident that pain management, regardless of the type of pain, should be tailored to the individual patient [ 40 , 60 ]. Moreover, the progress of knowledge on pain mechanisms, the results derived from clinical trials, and the development of new medical technologies have allowed researchers to improve the efficacy of the available therapies [ 60 , 61 , 62 , 63 , 64 ].…”
Section: The Pharmacological Approachmentioning
confidence: 99%